Intermolecular interactions of decamethoxinum and acetylsalicylic acid in systems of various complexity levels - O. V. Vashchenko; N. A. Kasian; V. A. Pashynska; M. V. Kosevich; A. O. Sadchenko; D. N. Tishko; T. V. Tishko; V. P. Titar; L. N. Lisetski (Біофізичний вісник, 2016)
Intermolecular interactions between decamethoxinum (DEC) and acetylsalicylic acid (ASА) have been studied in the phospholipid-containing systems of escalating complexity levels. The host media for these substances were solvents, L-α-dipalmitoylphosphatidylcholine (DPPC) membranes, and samples of human erythrocytes. Peculiar effects caused by DEC-ASА interaction have been observed in each system using appropriate techniques: (a) DEC-ASА non-covalent complexes formation in DPPC-containing systems were revealed by mass spectrometry with electrospray ionization; (b) joint DEC-ASА action on DPPC model membranes led to increasing of membrane melting temperature Tm, whereas individual drugs caused pronounced Tm decreasing, which was demonstrated by differential scanning calorimetry; (c) deceleration of DEC-induced haemolysis of erythrocytes under joint DEC-ASА application was observed by optical microscopy.